The Implementation of Fault Tree Analysis (FTA) dan Failure Mode And Effect Analysis (FMEA) to Improve the Quality of Salt Industry in East Java - Mansur Yafi, Muhammad; Cahyono, Muhammad Denny Nur (Universitas Nahdlatul Ulama Sidoarjo, 2024)
The problem in the salt processing industry is that product defect reach 15% of the total production so it is important to analyze the cause of the defects. The average product defect currently exceeds the company's target of 5%. The Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA) methods are used to analyze the production process at PT. XYZ. FTA is used to analyze the causes of each category of product defects, while FMEA is used to classify and analyze each cause of defects.